2016
DOI: 10.1002/smll.201670129
|View full text |Cite
|
Sign up to set email alerts
|

Silica Nanospheres: Hollow Structure Improved Anti-Cancer Immunity of Mesoporous Silica Nanospheres In Vivo (Small 26/2016)

Abstract: Hollow and non‐hollow mesoporous silica nanospheres are synthesized and used for cancer vaccine adjuvants by X. Wang, A. Ito, N. M. Tsuji, and co‐workers on page 3510. The hollow structure of mesoporous silica nanospheres significantly promotes cellular uptake of a model cancer antigen by macrophage‐like cells in vitro, improves anti‐cancer immunity, and increases CD4+ and CD8+ T cell populations in splenocytes of mice in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…MSNs present a number of excellent material properties, such as good in vitro and in vivo biocompatibility, chemical and mechanical stability, and easy functionalization ability . In fact, the favorable structural features of MSNs, such as intrinsic tunable pore size, high pore volume, and high surface area, could guarantee an extraordinary drug loading capacity and high encapsulation efficiency of a wide variety of cargo molecules . Additionally, their surfaces can be functionalized with “gate keepers,” some of which are highly sensitive to a variety of exogenous and endogenous stimuli, such as light, pH, temperature, and remote magnetic actuation, enabling controlled and on‐command release of the cargo …”
Section: Introductionmentioning
confidence: 99%
“…MSNs present a number of excellent material properties, such as good in vitro and in vivo biocompatibility, chemical and mechanical stability, and easy functionalization ability . In fact, the favorable structural features of MSNs, such as intrinsic tunable pore size, high pore volume, and high surface area, could guarantee an extraordinary drug loading capacity and high encapsulation efficiency of a wide variety of cargo molecules . Additionally, their surfaces can be functionalized with “gate keepers,” some of which are highly sensitive to a variety of exogenous and endogenous stimuli, such as light, pH, temperature, and remote magnetic actuation, enabling controlled and on‐command release of the cargo …”
Section: Introductionmentioning
confidence: 99%
“…Based on the extensive porous network, high specific surface area and excellent biocompatibility, mesoporous silica has emerged as a common drug carrier [27,28,29,30,31]. When mesoporous silica is incorporated in cellulose membrane, hierarchic pore structure will be attained inside the mesoporous matrix of the cellulose–silica membranes.…”
Section: Introductionmentioning
confidence: 99%
“…[ 13 ] Additionally, hollow MSNs were proven to increase the number of CD4 + and CD8 + T cells in spleen cells and promote antitumor immunity in vivo. [ 14 ] Some studies also have shown that MSNs can induce Th1 and Th2 immune responses, promote lymphocyte proliferation, and stimulate secretion of pro‐inflammatory cytokines, which is conducive to reverse the immunosuppressive tumor microenvironment (TME). [ 15 ] In short, MSNs are considered to be one of the most promising nanoadjuvant materials for various vaccine applications.…”
Section: Introductionmentioning
confidence: 99%